PKM PEGAWAI HOTEL DALAM PENERAPAN PROTOKOL KESEHATAN - Budiapsari, Putu Indah; Widhidewi, N. W. (Buletin Udayana Mengabdi, 2021)
With the opening of the Bali tourism faucet during the new normal era and the increasing number of domestic visits, it is necessary to implement good and correct health protocols in lodging locations such as hotels, villas, homestays, guest houses and so on. In an effort to keep tourism running and the spread of Covid-19 can be reduced. The online marketing strategy will also increase the income of hotel employees and the level of room reservations. Furthermore, with all the preparations that have been made, we survey, observe, map, determine and assign groups of hotel employees. To add to the completeness of the data, we conducted interviews with the head of the partners who knew how the activities of the employees and guests of the hotel were. Solutions in the health sector by making transparent barriers that will limit the droplet transmission of hotel guests and receptionists, setting distances by placing a cross in certain places, providing sinks and water for washing hands, implementing screening rules with thermoguns at the entrance, distributing masks standards recommended by WHO, counseling and training on how to wash hands 6 steps with no-touch technique. Keywords : Protocol, health, hotel, marketing, online